2015
DOI: 10.1007/s00210-015-1134-1
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the pharmacodynamics of the SGLT2 inhibitor empagliflozin in animals and humans

Abstract: Empagliflozin (formerly known as BI 10773) is a potent, competitive, and selective inhibitor of the sodium glucose transporter SGLT2, which mediates glucose reabsorption in the early proximal tubule and most of the glucose reabsorption by the kidney, overall. Accordingly, empagliflozin treatment increased urinary glucose excretion. This has been observed across multiple species including humans and was reported under euglycemic conditions, in obesity and, most importantly, in type 2 diabetic patients and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 66 publications
3
50
0
2
Order By: Relevance
“…Therefore, number and type of preclinical studies performed prior to regulatory approval of new drugs are likely to differ considerably. Comparison between the few cases where comprehensive reviews were published summarizing non-clinical data (Eberlin et al 2012;Michel et al 2015;Modjtahedi et al 2014) supports the notion that preclinical strategies may differ considerably, but overall little empirical data is available in this regard.…”
Section: Introductionmentioning
confidence: 63%
“…Therefore, number and type of preclinical studies performed prior to regulatory approval of new drugs are likely to differ considerably. Comparison between the few cases where comprehensive reviews were published summarizing non-clinical data (Eberlin et al 2012;Michel et al 2015;Modjtahedi et al 2014) supports the notion that preclinical strategies may differ considerably, but overall little empirical data is available in this regard.…”
Section: Introductionmentioning
confidence: 63%
“…Oral antidiabetic drugs are the cornerstone of T2DM treatment, but none of them has been tested for effects on bladder hypertrophy. In this regard, SGLT2 inhibitors may be of specific interest because they promote glycosuria . More treatment studies, particularly involving drugs in clinical use for the treatment of T2DM, are urgently needed.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…In a recent survey of academic investigators engaging in project-based, non-clinical collaboration with the pharmaceutical industry, complex contract negotiations were seen as a major hurdle for collaboration, interestingly equally being attributed to legal departments of companies and academic institutions (Amiri and Michel, 2015). Other case studies of project-based collaborations in drug development have recently been reported (Modjtahedi et al, 2014; Michel et al, 2015). Academic investigators engaged in non-clinical drug-related research expressed strong interest in such collaborations (Amiri and Michel, 2015).…”
Section: Types Of Public–private-partnershipsmentioning
confidence: 99%
“…Aspects of non-clinical investigator-initiated research have been discussed in the previous section and reviewed elsewhere (Modjtahedi et al, 2014; Michel et al, 2015; Michel and Korstanje, 2016) Focusing on clinical IIS, Stefan Schröder and Miriam Bach (Bayer, Berlin, Germany) reported that the investigator is responsible for initiating, managing and financing the study, following applicable laws and regulations. These include the rules of Good Clinical Practice and Good Manufacturing Practice as well as article 2 (e) of the European Directive 2001/20/EC.…”
Section: Types Of Public–private-partnershipsmentioning
confidence: 99%